2013
DOI: 10.1002/ajpa.22403
|View full text |Cite
|
Sign up to set email alerts
|

Manual lateralization in wild redfronted lemurs (Eulemur rufifrons) during spontaneous actions and in an experimental task

Abstract: The dominant use of one hand is a striking feature of humans, but manual lateralization can be found in a variety of other species as well. In primates, the lateralization in hand use varies among species and several theories such as the "postural origin," "task complexity," or "development theory" have been suggested to explain this variation. In order to contribute comparative data on this phenomenon from a basal primate, we studied manual lateralization in wild redfronted lemurs (Eulemur rufifrons). Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
0
17
1
Order By: Relevance
“…In the case of methodological issues, the objection seems to boil down to the type of tasks used for measuring hand preference. In general, tasks that do not require cognitive and motor demanding actions, such as the commonly‐used manual reaching for food, hardly evoke hand preference in non‐human primates (Fagot & Vauclair, ; Papademetriou et al, ; Schnoell, Huebner, Kappeler, & Fitchel, ). According to the task complexity hypothesis, proposed by Fagot & Vauclair (), high‐level tasks, that is, those needing cognitively demanding requirements, tend to elicit stronger hand preference in non‐human primates, although this hypothesis does not make predictions about direction of hand preference.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of methodological issues, the objection seems to boil down to the type of tasks used for measuring hand preference. In general, tasks that do not require cognitive and motor demanding actions, such as the commonly‐used manual reaching for food, hardly evoke hand preference in non‐human primates (Fagot & Vauclair, ; Papademetriou et al, ; Schnoell, Huebner, Kappeler, & Fitchel, ). According to the task complexity hypothesis, proposed by Fagot & Vauclair (), high‐level tasks, that is, those needing cognitively demanding requirements, tend to elicit stronger hand preference in non‐human primates, although this hypothesis does not make predictions about direction of hand preference.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature on lemur manual lateralization, the finding of a group‐level hand preference is quite unusual. Indeed, prior studies on this topic usually failed to reveal a significant bias in hand use for simple reaching and other unimanual actions [Leliveld et al, ; Lhota et al, ; Rigamonti et al, ; Schnoell et al, ], although it has been reported a tendency toward a left‐handedness in strepsirrhines [for review, see: Ward et al, ], including a sample of ring‐tailed lemurs [Milliken et al, ; Shaw et al, ]. However, as mentioned above, most studies on strepsirrhine hand preference have relied on the measurement of simple and spontaneous actions.…”
Section: Discussionmentioning
confidence: 99%
“…In both the unimanual and bimanual task, bouts of hand preference were considered, meaning that only the hand starting an action subset was recorded, to guarantee independence of data points [McGrew & Marchant, ; Schnoell et al, ]. To avoid a learning effect on lemur hand preference, each session was limited to a maximum of five trials; a new trial was considered only after the lemur finished interacting with the apparatus, changed its posture or was in a symmetrical position (in front of the apparatus).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations